Predicting Liver‐Related Outcomes in People With Nonalcoholic Fatty Liver Disease: The Prognostic Value of Noninvasive Fibrosis Tests. Issue 4 (15th November 2021) - Johnson, Amy L.; Hayward, Kelly L.; Patel, Preya; Horsfall, Leigh U.; Cheah, Alvin Ee Zhiun; Irvine, Katharine M.; Russell, Anthony W.; Stuart, Katherine A.; Williams, Sue; Hartel, Gunter; Valery, Patricia C.; Powell, Elizabeth E.
Abstract : It remains unclear whether screening for advanced fibrosis in the community can identify the subgroup of people with nonalcoholic fatty liver disease (NAFLD) at higher risk for development of liver‐related complications. We aimed to determine the prognostic value of baseline noninvasive fibrosis tests for predicting liver‐related outcomes and mortality in patients with NAFLD from type 2 diabetes (T2D) clinics or primary care. Patients (n = 243) who were screened for NAFLD with advanced fibrosis by using NAFLD fibrosis score (NFS), fibrosis 4 score (FIB‐4), enhanced liver fibrosis (ELF) test, and liver stiffness measurements (LSMs) were followed up for clinical outcomes by review of electronic medical records. During a median follow‐up of 50 months, decompensated liver disease or primary liver cancer occurred in 6 of 35 (17.1%) patients with baseline LSM > 13 kPa, 1 of 17 (5.9%) patients with LSM 9.5‐13 kPa, and in no patients with LSM < 9.5 kPa. No patient with low‐risk NFS developed liver decompensation or liver‐related mortality. Following repeat NFSs at the end of follow‐up, all patients with a liver‐related complication were in the high‐risk NFS category. Patients who developed liver‐related complications were also more likely to have baseline high‐risk FIB‐4 scores or ELF test ≥9.8 compared to patients who did not develop liver outcomes. Conclusion: Liver fibrosis risk stratification in non‐hepatology settings can identify the subset of patients at risk of liver‐related complications. Although the rate of development of a decompensation event or hepatocellular carcinoma was low (2.1% per year) in our patients with compensated cirrhosis (LSM > 13 kPa), these events are projected to lead to a substantial increase in NAFLD‐related disease burden over the next decade due to the high prevalence of NAFLD in people with obesity and T2D. Abstract : image